Who's who in Nigeria (Lagos, Nigeria Nigerian International Bibliographical Centre, 2006)
The publication profiles more than 5000 notable Nigerians who stand out in a remarkable way: leaders in commerce and industry, politics and policy, noted academics and other professionals, religious leaders and artist of repute.
osc 8/12/2021
Ref
Keywords: Who's who; Nigeria